2015
DOI: 10.1177/0969733015594666
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of School of health students' ethics position in Turkey

Abstract: It is suggested that the courses and practices that teach students to be aware of their ethics position to create an ethical outlook can be placed in the curriculum in health schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 26 publications
0
14
0
5
Order By: Relevance
“…These findings correspond to similar findings in other studies showing that nursing students differ in terms of relativism. 61 Similarly, the mean relativism scores of nursing students in terms of year of study differ significantly. This finding corresponds to similar findings in other studies showing that nursing students differ in terms of year of study on a measure of relativism.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These findings correspond to similar findings in other studies showing that nursing students differ in terms of relativism. 61 Similarly, the mean relativism scores of nursing students in terms of year of study differ significantly. This finding corresponds to similar findings in other studies showing that nursing students differ in terms of year of study on a measure of relativism.…”
Section: Discussionmentioning
confidence: 97%
“…This finding corresponds to similar findings in other studies showing that nursing students differ in terms of year of study on a measure of relativism. 61 Smith 53 observed that the ethical ideology of nursing students change from being idealistic at the beginning of their programme to a loss of idealism as they become more exposed to the reality of clinical practice in nursing. Such a development, Smith 53 concluded, can have negative consequences for caring in nursing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral orientation using Forsyth’s EPQ was recently studied with two groups of Turkish health professionals, midwives and students of disaster management. 13 Although the mean scores for the subscale on idealism did not differ between the two fields of study, the mean scores significantly differed between the years of study. However, the mean scores for the subscale on relativism did not differ in terms of the years and fields of study.…”
Section: Personal Moral Philosophy: Ethics Positionmentioning
confidence: 83%
“…19 While the relationship between ethics and law is well established, the recognition of reproductive rights 20 and more recently human rights in childbirth, 21,22 evidence of how a human rights framework for midwifery care 7 is incorporated within midwifery education is unknown since the discussion of the provision of ethics education for midwives and student midwives is limited in the literature. 23,24 Others have recently attempted to address this by developing a model to increase ethical competence for education and practice. 25…”
Section: Introductionmentioning
confidence: 99%